The Impact of the September 11 Attack on Insurance Companies - Liu, Shanshan (Université d'Ottawa | University of Ottawa, 2003)
On September 11, 2001, terrorists launched a devastating attack against the United States using four commercial airplanes fully loaded with jet fuels as lethal weapons, and both the 110-story towers of the World Trade Center in New York City collapsed. Du